(untitled) (GAIMS Journal of Medical Sciences, 2021)
Aniridia is a familial or sporadic disorder affecting not only the iris but also the cornea, angle structures, lens, optic nerve, and fovea. This disorder may be associated with many other systemic abnormalities such as urogenital malignancies. We report a family of aniridia with different clinical spectrum of features.